Micronations and the search for sovereignty - Hobbs, Harry (Writer of Indigenous aspirations); Williams, George, 1969- (Cambridge : Cambridge University Press, 2022)
Political disagreement is a fact of life. It can prompt people to stand for public office and agitate for political change. Others take a different route; they start their own nation. Micronations and the Search for Sovereignty is the first comprehensive examination of the phenomenon of people purporting to secede and create their own country. It analyses why micronations are not states for the purposes of international law, considers the factors that motivate individuals to separate and found their own nation, examines the legal justifications that they offer and explores the responses of recognised sovereign states. In doing so, this book develops a rich body of material through which to reflect on conventional understandings of statehood, sovereignty and legitimate authority. Authored in a lively and accessible style, Micronations and the Search for Sovereignty will be valuable reading for scholars and general audiences.
Prince Leonard prepares for war -- Statehood and micronations -- Motivations -- Performing sovereignty -- State responses -- The future of micronationalism -- List of micronations discussed.
Title from publisher's bibliographic system (viewed on 28 Dec 2021).
Keywords: Sovereignty; Nation-building.; Sealand (Wales) -- History